CHANGE AND THE INTERNET - Kjaerulff, Jens. Link (ABINGDON)
1 online resource
Keywords: This book explores the significance of new information technology for socio-cultural change and provides ethnographic insight into the early days of remote working. It draws on long-term anthropological fieldwork among people in rural Denmark working from home via the internet. Going back to the late 1990s and early 2000s, the study demonstrates how remote and flexible working was mostly practiced informally, fostering incremental changes to the cultural domain of 'work'. It captures the dilemmas arising from living with multiple arenas and the challenges of balancing work and family life - a predicament which motivates many to embrace remote working. The volume contains an updated introduction and conclusion where the author reflects on the historical moment of his fieldwork and on the impact of the recent Covid-19 pandemic on working practices. The book offers a valuable comment on how to empirically study the social and cultural significance of new information technologies, as well as how to think of and empirically research change anthropologically, situating information technology in a broader offline context of unfolding complex living. It will be of interest to scholars of social anthropology and digital ethnography, as well as others with a focus on social aspects of information technology and on work and organizational studies.